Effect of Nitrogen Levels, Moisture Regimes and Soil Texture on Growth and Nutrients Uptake by Sissoo (Dalbergia Sissoo) Saplings - Singh, R.A.; Muhamad, S. (Journal of Soil and Water Conservation, 2022)
About 80% of the forest areas of Bihar right burdened and very closely interpersed with human population coupled with large number of cattle population dependant on forest lands for grazing. This has adversely affected the soil fertility due to destruction of ground flora. Therefore, for proper growth of new plantations, fertility and water management of the forest soils are necessary.